Systematic review of pharmacotherapy for atypical facial pain: evaluation of pain reduction, depression, anxiety and quality of life - Abdullah F. Alshammari; Hind M. Alassaf; Ahmed A. Madfa; Sattam S. Alshammari; Sameer Shaikh; Hassan H. Abed; Ali A. Alqarni; Freah L. Alshammary; Khlood A. Alkurdi (Annals of Medicine)
Background/purpose Atypical facial pain (AFP) is a chronic condition characterized by persistent facial pain without clear clinical signs, making diagnosis and treatment difficult. Common pharmacological treatments include antidepressants, anticonvulsants and neuromodulators, but their effectiveness remains uncertain, necessitating a systematic review to guide clinical practice.Materials and methods Following PRISMA 2020 guidelines, randomized controlled trials (RCTs) evaluating pharmacological treatments for AFP in adults were included. A comprehensive search of five databases without date restrictions was performed. Data on pain reduction, quality of life, and adverse events were extracted. The Cochrane Risk of Bias (RoB 2.0) tool assessed bias, and evidence quality was evaluated using the Critical Appraisal Skills Programme tool.Results Out of 196 studies identified, 10 RCTs met the inclusion criteria. Pharmacological responses varied significantly across studies. Antidepressants such as dothiepin and clomipramine demonstrated significant pain reduction, whereas venlafaxine showed limited efficacy. However, onabotulinum toxin A and sumatriptan exhibited inconsistent or minimal effects on AFP pain intensity. Adverse events were reported across multiple treatments, ranging from mild side effects such as dry mouth and nausea to severe reactions like diplopia and facial asymmetry, which impacted adherence. Despite some positive outcomes, the heterogeneity in study methodologies, outcome measures, and follow-up durations limited direct comparisons between interventions.Conclusion This systematic review highlights the mixed efficacy of pharmacological treatments for AFP, with certain medications demonstrating superior pain relief in specific patient subgroups. Given the variability in response and adverse events, a multimodal approach combining pharmacological and non-pharmacological therapies may offer the most effective management strategy. Future research should focus on standardized treatment protocols, long-term efficacy, and personalized treatment plans to optimize patient care.